(untitled) (Orfeu, 2017)
The purpose of this article is to trace the social and musical relevance of the event known as “Tocata”, in Florianópolis/ SC. Proposed as an informal meeting, open and not restricted to musicians, the Tocata opens itself as a shared experience that favors different potentialities of musical making, as well as the reinvention of the relationship that participants have with music. Given this specificity of the interactions and the human conviviality, as they occur there, the Tocata allows us an artistic-musical experience that occurs in the becoming of a creative, simultaneous and collective process, where the musical action intends to present itself in an affective, spontaneous and intuitive way. The data of the research is taken from reports of participants registered between 2015 and 2016 for the Final Paper (TCC): Experimental Conviviality and Musical Improvisation in the Tocata: the production of an ethico- -aesthetic attitude. We have placed these reports in articulation with our own experience, as participants and researchers in the field of music and visual arts, and in dialogue with these fields we introduce descriptions of the Tocata and reflections that have accompanied us during the last years.